2000
DOI: 10.1155/s1064744901000059
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Obstetrician‐Gynecologists in the United StatesAbout Toxoplasmosis

Abstract: Background: Although the incidence of toxoplasmosis is low in the United States, up to 6000 congenital cases occur annually. In September 1998, the Centers for Disease Control and Prevention held a conference about toxoplasmosis; participants recommended a survey of the toxoplasmosis-related knowledge and practices of obstetrician-gynecologists and the development of professional educational materials for them

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
4

Year Published

2006
2006
2025
2025

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 18 publications
2
32
0
4
Order By: Relevance
“…Apenas 11% das gestantes suscetíveis relataram ter recebido orientações profiláticas em todas as consultas de pré-natal. Estudo prévio realizado nos Estados Unidos demonstrou que 96% dos obstetras orientaram verbalmente suas pacientes 25 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Apenas 11% das gestantes suscetíveis relataram ter recebido orientações profiláticas em todas as consultas de pré-natal. Estudo prévio realizado nos Estados Unidos demonstrou que 96% dos obstetras orientaram verbalmente suas pacientes 25 .…”
Section: Discussionunclassified
“…E, por mais que numerosos estudos tenham demonstrado que o contato com gato seja um fator de risco secundá-rio na transmissão da toxoplasmose, ao contrário da ingestão de carne crua 26 , foi observado que a proporção de mulheres informadas em relação ao gato (95%) foi muito superior ao número de informadas sobre o risco de consumo da carne crua (70%) e hortaliças cruas inadequadamente lavadas (53%). Estudos prévios realizados nos Estados Unidos também apontaram o contato com os gatos como fonte de infecção mais citada entre os médicos 25,27 .…”
Section: Discussionunclassified
“…Not only is the lack of reliability of such test kits a problem, but use of results in the IgM assays to guide care of the pregnant woman by obstetricians in the United States, and probably elsewhere as well, is not always well informed. For example, Jones and associates [709] reported that 364 of 768 (47%) American College of Obstetrics and Gynecology (ACOG) members responded to a survey regarding their knowledge of toxoplasmosis in pregnant women and related OB-GYN practices. In the previous year, 7% diagnosed one or more cases of acute toxoplasmosis, and only 12% indicated that a positive Toxoplasma IgM test might be a false-positive result.…”
Section: Demonstration Of Specific Immunoglobulin M Antibodiesmentioning
confidence: 99%
“…In studying the altitudes and practices of respondents, 52.7 % and 47.6 % of health professionals thought toxoplasmosis as important pathogen in HIV infected patients and pregnant women respectively but Less than half of professionals, 44.4 %, knew the medication of toxoplasmosis in pregnant and neonates but 22.3 of respondents they don't knew what they do if pregnant women and neonats became toxoplasmosis positive. (10) 18 (90) 2(10) 2(33.3) 4(66.7) 93 (93) 7(7) 0.000* Comparing the number of answers according to type of profession, the professionals who are gynecologist and physician showed the total number of correct answers on the issues of clinical manifestation, prevention and diagnosis, higher than those who are nurses however nurses had a better experience (23 %) of using laboratory test relative to other professionals.…”
Section: Socio Demographic Characteristics Of Health Professionalsmentioning
confidence: 99%
“…A survey showed that the vast majority of obstetricians counselled pregnant women on avoiding cat litter and undercooked or raw foods, but fewer provided counselling on safe gardening and over 50 % responded that keeping a cat outdoors would lower the risk of toxoplasmosis [JONES et al, 2001] . Education of obstetricians, nurses and physician on risk factors for toxoplasmosis transmission is needed and may lower the rate of congenital toxoplasmosis as well as decrease the frequency of cat abandonment during pregnancy.…”
Section: Introductionmentioning
confidence: 99%